How Much Will They Buy? Optimal Forecast Selection for Predicting a Bakery’s Demand - Vally, Mohammed Alli (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Mini Dissertation (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2018.